PERSEPSI PEMERIKSA TENTANG PERENCANAAN PROSEDUR PEMERIKSAAN LAPORAN KEUANGAN PEMERINTAH DAERAH (STUDI PADA BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA ) - , Cancerto Klaudius Windarto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to identify perceptions of BPK RIâs auditors to the planning of Local Government Financial Report (LKPD) audit procedure. By procedure, LKPD is audited annually by the BPK RI branch offices in accordance with the prevailing Acts. Usually auditors do not have adequate time for the planning. Thus accuracy is crucial in planning the LKPD audit. The referred planning is the planning of examining internal control system and substantial examination on transactions and account balances. This study is conducted using questionnaire, with purposive sampling method. Sample of this survey are BPK RI auditors assigned in provincial offices in Java who had audited the LKPD. The questionnaire record targeted auditorsâ perceptions in Likert scale as a response to the provided statements. The finding is analyzed based on the predefined criteria. As a result, this study shows that the perceptions of BPK RIâs auditor to the planning of LKPD audit procedures are good in general and already in accordance with the principles of professionalism, honesty, and fairness.